FABRICATION TECHNIQUE OF DENTAL RESTORATION USING HYBRID CERAMIC WITH CAD CAM METHOD - Andriyani, Meita; Harwasih, Sonya; Inayati, Eny (Journal of Vocational Health Studies, 2017)
Background:  Ceramic is superior in aesthetic but fragile and breakable under bite pressure . Lack of understanding of material requirements for resistance in the oral cavity and minimal ceramic processing techniques is the initial cause of the failure. Hybrid ceramic dental restoration is a material that combines the good properties of ceramics and composites that have elasticity and ensures high strength and minimize the wall thickness of the restoration. Mechanical manufacture of dental restorations currently growing, CAD CAM systems are becoming popular in the field of dentistry. CAD CAM provides the advantage that the effectiveness of the time, does not require a lot of human resources, and produce a restoration with good quality. Purpose:  To explain hybrid ceramic material and techniques of making  hybrid ceramic dental restorations with CAD CAM system. Review: Hybrid ceramic is a material that combines the advantages of ceramics and composite elasticity. This material contains a hybrid structure with two networks, ceramic and polymer are linked to each other, known as double hybrid network. It added that the structure of the ceramic feldspathic network (86% wt) is reinforced by a polymer network (14% wt) are integrated as a polymer network filling cavities that exist in the network and make its structure ceramic hybrid ceramic material becomes denser. Conclusion: Hybrid ceramic having chewing load capacity and high elasticity, flexural strength  150-160 Mpa and fracture toughness 1.5 Mpa, higher than conventional ceramics. Mechanical manufacture of dental restorations using ceramic hybrid materials with CAD CAM method begins with scanning, selection of materials and tooth shade, designing, milling, followed by finishing, polishing, ends with staining and glazing.